Optimal foraging by a large ungulate in an extreme environment: Wild mountain reindeer select snow‐free feeding habitats in winter. Issue 15 (5th July 2021) - Romtveit, Lena; Strand, Olav; Mossing, Anders; Kastdalen, Leif; Hjeltnes, Arne W.; Bjerketvedt, Dag K.; Odland, Arvid; Heggenes, Jan
Abstract: Optimal foraging models predict that individual animals will optimize net energy gain by intensifying forage activity and/or reducing forage energy cost. Then, the free distribution model predicts an animal's distribution in a patchy landscape will match the distribution of the resources. If not modified by other factors, such patterns may be expected to be particularly explicit in variable and extreme, forage‐limited, and patchy environments, notably alpine and Arctic environments during winter. The large ungulate wild mountain reindeer ( Rangifer tarandus tarandus ) surviving in such environments is used as a model during the forage‐limited winter season. The largest wild reindeer area in Western Europe (Hardangervidda, 8130 km 2 ) is actively managed to sustain 10, 000–12, 000 wild reindeer. Since 2001, 104 different individuals have been GPS‐tracked at 3‐hr intervals. In winter, mountain reindeer may either choose to seek out and forage in patchy snow‐free habitats, typically on top of wind‐blown ridges, or use energy‐demanding digging through the snow to reach ground forage (cratering). We use late April satellite data from Landsat 5 and 8 (30 × 30 m), airborne laser scanning subsampling (processed to 1 × 1 m grid), and topographic information (1 m resolution) derived from digital aerial photographs (0.25 × 0.25 m resolution) to delineate snow‐free patches, constituting less than 694 km 2 . By overlaying recorded wild reindeer GPS positions winters 2001–2017 (188, 942 positions), we document a strong positive selection for snow‐free patches, which were used about four times more frequently than expected from a "random walk" model. On a daily basis, the preference for snow‐free areas was slightly stronger in the evenings. In the sustainable management of wild mountain reindeer, the area of snow‐free patches is an important predictor of winter forage availability and important winter source areas. It may be derived from remote sensing data. Abstract : Remote sensing data were used to delineate typically snow‐free or near snow‐free patches within a 8, 600 km 2 alpine mountain reindeer area. Comparison with wild reindeer GPS positions across winters 2001–2017 documented a strong positive selection for snow‐free patches (four times more use). In the sustainable management of wild mountain reindeer, area of (near) snow‐free snow‐free patches is an important predictor of winter carrying capacity.